P123 Accuracy and Reliability of the Transcutaneous Carbon Dioxide (TcCO2) Signal in the Sleep Laboratory. (7th October 2021) - Rossely, A; Turton, A; Roebuck, T; Ho, S; Naughton, M; Mansfield, D; Hamilton, G
Abstract: Carbon Dioxide (CO2) monitoring is an essential part of assessing and treating disorders of hypoventilation in the sleep laboratory. While reliablity issues have been previously reported with the Transcutaneous Carbon Dioxide (TcCO2) signal, there is limited data assessing the validity of this signal or its trend in the sleep laboratory context. Therefore, this study aimed to investigate the change in TcCO2 accuracy from the beginning to the end of the sleep study in real world conditions across two different Victorian public hospital sleep laboratories that used two different TcCO2 monitors. The sample included 13 consecutive patients from Monash Health and 44 consecutive patients from Alfred Health with an average age of 64 and 56 years respectively. Arterial Blood Gas (ABG) measurements were taken prior to and following each sleep study and compared concurrently with the TcCO2 value. Bland-Altman analysis revealed an average difference between TcCO2 and PaCO2 of 3.29mmHg with agreement between -11.44 and 16.64mmHg for the TCM4 device and 1.31mmHg with agreement between -7.64 and 9.05mmHg for the TCM5 device. When accuracy was compared across time points for each patient, 46% of patients had an overnight accuracy change of ≥ 8mmHg when using the TCM4 compared with 20% when using the TCM5. It was concluded that the TcCO2 signal was un-reliable across the different monitors and that the TcCO2 trend may be difficult to interpret with confidence without blood gas calibration at the commencement and conclusion of the sleep study.